Magazine Notes for the Work Social: A Look to Them Women Intellectuals of the Ngo and the Generation of Knowledge on It Popular-Feminine in Chile, 1980-1989 [Revista Apuntes Para el Trabajo Social: Una Mirada a Las Mujeres Intelectuales de Las Ong y la Generación de Conocimiento Sobre Lo Femenino-Popular en Chile, 1980-1989] - Moyano-Barahona, C (Universidade Estadual Paulista, 2018)
The following article aims to give an account of how a group of social workers linked to various NGOs during the chilean s dictatorship, they built, on the one hand, knowledge about their field of expertise, and on the other, on the conditions of the popular women. Based on these reflections and debate that were installed in the magazine Notes for the work Social, belonging to the collective of Social work, these women stressed cultural models of gender force installing the theme in the political agenda of the sectors of the opposition to the dictatorship. Of this way, the study of the praxis of these intellectual of them movements of women is returns relevant in the measure that us delivery signs from where can understand them transformations cultural of the world popular from them relations of gender. © 2018 Universidade Estadual Paulista.; El siguiente artículo busca dar cuenta de cómo un grupo de trabajadoras sociales vinculadas a distintas ONG durante la dictadura chilena, construyen, por una parte, conocimiento sobre su campo de experticia y, por otra, sobre las condiciones de las mujeres populares. A partir de estas reflexiones y del debate que instalaron en la revista Apuntes para el Trabajo Social, perteneciente al Colectivo de Trabajo Social, estas mujeres tensionaron los modelos culturales de género vigentes instalando el tema en la agenda política de los sectores de oposición a la dictadura. De esta manera, el estudio de la praxis de estas intelectuales de los movimientos de mujeres se vuelve relevante en la medida que nos entrega indicios desde donde poder comprender las transformaciones culturales del mundo popular desde las relaciones de género. © 2018 Universidade Estadual Paulista.